The Next Level of Purchase Intention - Elfindah Princes , Adler Haymans Manurung , Idris Gautama So , Sri Bramantoro Abdinagoro (International Journal of Advanced Science and Technology, 2020)
Purchase Intention is always associated with the capabilities of the firms to approach the customers through brand image, commercial activities and how firms provide excellent service to increase customer satisfaction and increase the purchase intention probability for the next product release. Customers are viewed as the object of firms’ organizational activities to provide benefits for the company. The researcher broadens this view into a bigger perspective, where the customers are now not only becoming the objects, but also the subjects of the organizational activities. The purchase intention must move on to the next level where all actors in organizational activities are taking charge in delivering purchase intention. Human - to - human interaction has become so important in organizational activities that firms must articulate on these factors to complement the existing factors, especially during the Industry 4.0. This research uses a quantitative analysis with 91 respondents aged between 18 to 55 years old with income. The data analysis uses SPSS AMOS. The findings correlate with the newest Consumer Trend Report for 2020 and more that in the future, social interaction between humans takes a great deal in making purchase decisions, known as consumer conformity. Innovations must be done by gaining consumer insights and increasing social roles to the advantages of the firms through social comparison, image related concerns and strategic complements. This research has several limitations. First, data collection was based on convenience sampling and the second, the ideal number of respondents should be 385 based on Cochran’s sampling method calculation. Future research should address these two issues.